INTEGRAL ASSESSMENT OF EFFICIENCY OF A FLEET OF AGRICULTURAL MACHINERY AND TRACTORS - V. M. Korotchenya (Сельскохозяйственные машины и технологии)
An indicator for an integral assessment of efficiency of a fleet of agricultural machinery and tractors is proposed. Its calculating consists in multiplying partial efficiencies together: technical and price efficiency of agricultural production, and eco-efficiency of a fleet of agricultural machinery and tractors. Using an axiomatic method, the concept of efficiency of fleet was studied within broader category of productivity and in wider scales - within agriculture. The most general and obvious statements according to which efficiency of machine and tractor fleet is considered as indirectly settlement size counted proceeding from efficiency of agricultural production, were accepted as axioms. In general, efficiency is a ratio between productivity of an object in question and that of the theoretical ideal or an object with maximum productivity efficiency of which is accepted equal to unity or 100%. Technical efficiency of agricultural production characterizes the ability of an agricultural sector to produce the technically maximum output of agricultural produce obtained from the available resources (land, labor, machines, etc.). Price efficiency evaluates the ability of an agricultural sector to produce output of agricultural produce with regard to employing the optimal mix of resources given their prices. Because the theoretical ideal does not exist, efficiency of an agricultural sector, e.g. in Russia and of its fleet of agricultural machinery and tractors, is measured against agriculture of another country with maximum productivity efficiency of which is accepted as equal to unity or 100 percent. The calculation can be made on the basis of the Data Envelopment Analysis method. It is possible to calculate price and economic efficiency of Russian agriculture (fleet of agricultural machinery and tractors) due to use its domestic prices.